2015
DOI: 10.1016/j.jhazmat.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Vapor intrusion attenuation factors relative to subslab and source, reconsidered in light of background data

Abstract: The basis upon which recommended attenuation factors for vapor intrusion (VI) have been derived are reconsidered. By making a fitting curve to the plot showing the dependence of observed indoor air concentration (cin) on subslab concentration (css) for residences in EPA database, an analytical equation is obtained to identify the relationship among cin, css and the averaged background level. The new relationship indicates that subslab measurements may serve as a useful guide only if css is above 500 μg / m3. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Therefore when the traditional CST equation is used to predict short-term maximum indoor air concentrations, more conservative input parameters should be employed than those usually adopted to predict the health risks of petroleum products. Moreover, according to the statistical analysis of U.S. EPA’s VI database by EPA and other researchers, after minimizing the influences of background sources, the observed subslab-to-indoor air concentration attenuation factors varies from 1 to 10 −4 (34, 44). It should be noted that most datasets recorded in U.S. EPA’s VI database were obtained at sites contaminated by chlorinated chemicals, and in those cases there should be no upward advective soil gas flow that can increase the soil gas entry rate into the building (and the subslab-to-indoor air concentration attenuation factor).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore when the traditional CST equation is used to predict short-term maximum indoor air concentrations, more conservative input parameters should be employed than those usually adopted to predict the health risks of petroleum products. Moreover, according to the statistical analysis of U.S. EPA’s VI database by EPA and other researchers, after minimizing the influences of background sources, the observed subslab-to-indoor air concentration attenuation factors varies from 1 to 10 −4 (34, 44). It should be noted that most datasets recorded in U.S. EPA’s VI database were obtained at sites contaminated by chlorinated chemicals, and in those cases there should be no upward advective soil gas flow that can increase the soil gas entry rate into the building (and the subslab-to-indoor air concentration attenuation factor).…”
Section: Resultsmentioning
confidence: 99%
“…AAMLPH can also be employed to estimate a conservative indoor air concentration C in by using a generic subslab-to-indoor air concentration attenuation factor αssin as 0.02 [37–38]. Figure 6 shows sensitivity test of 1r in predicting the maximum subslab soil gas concentration.…”
Section: Resultsmentioning
confidence: 99%
“…For example, 50 and 100 µ g / m 3 have been employed as the risk-based screening levels for soil vapor concentration of benzene [39]. Besides the risked-based screenings, a contribution-based screening was proposed recently to identify the dominant sources responsible for the indoor air contaminants [37]. It was reported that there is a greater likelihood that C in is determined by VI instead of background sources if C ss >500 ug / m 3 [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing awareness of the problem, as evidenced by numerous studies of the problem in the past two years, e.g. (Beckley et al, 2014; Brusseau et al, 2013; Dawson, 2013; Goreham et al, 2014; Holton et al, 2015; Johnson et al, 2014; Johnston and Gibson, 2014; Jourabchi et al, 2013; Lowe et al, 2015; Marchant, 2014; Perron et al, 2013; Schumacher and Zimmerman, 2013; Verginelli and Baciocchi, 2014; Yao et al, 2013c; Yao et al, 2015), there remains a strong impetus to better quantitatively characterize vapor intrusion processes.…”
Section: Introduction and Review Of Transient Indoor Air Contaminamentioning
confidence: 99%